2006
DOI: 10.1037/1040-3590.18.1.49
|View full text |Cite
|
Sign up to set email alerts
|

The reliability and validity of the Panic Disorder Self-Report: A new diagnostic screening measure of panic disorder.

Abstract: This study examined the Panic Disorder Self-Report (PDSR), a new self-report diagnostic measure of panic disorder based on the 4th edition of the Diagnostic and Statistical Manual of Mental Disorders (American Psychiatric Association, 1994). PDSR diagnoses were compared with structured interview diagnoses of individuals with generalized anxiety disorder, social phobia, and panic disorder and nonanxious controls. Receiver operating characteristic analyses revealed that the PDSR showed 100% specificity and 89% s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 80 publications
0
34
2
Order By: Relevance
“…The PDSS-SR is a 7-item self-report assessment of overall panic disorder severity, modified from the original clinician-administered PDSS (Shear et al, 1997). The PDSS-SR has demonstrated excellent internal consistency (˛= .92; Houck et al, 2002); good two-week retest reliability (r = .84; Newman, Holmes, Zuellig, Kachin, & Behar, 2006); and has demonstrated excellent sensitivity to cognitive-behavioral therapy for panic disorder (Houck et al, 2002;Penava, Otto, Maki, & Pollack, 1998), providing support for construct validity.…”
Section: Methodsmentioning
confidence: 98%
“…The PDSS-SR is a 7-item self-report assessment of overall panic disorder severity, modified from the original clinician-administered PDSS (Shear et al, 1997). The PDSS-SR has demonstrated excellent internal consistency (˛= .92; Houck et al, 2002); good two-week retest reliability (r = .84; Newman, Holmes, Zuellig, Kachin, & Behar, 2006); and has demonstrated excellent sensitivity to cognitive-behavioral therapy for panic disorder (Houck et al, 2002;Penava, Otto, Maki, & Pollack, 1998), providing support for construct validity.…”
Section: Methodsmentioning
confidence: 98%
“…The responses to the items are expressed on a 5-point Likert scale ranging from 0 (none) to 4 (extreme), and summed to create an overall severity score (range 0-28). Psychometric studies revealed excellent internal consistency (Cronbach's alpha: >9; Houck et al, 2002;Newman, Holmes, Zuellig, Kachin, & Behar, 2006), good two-week test-retest reliability (r = .84; Newman et al, 2006), and sensitivity to change after treatment (Houck et al, 2002). With a cut-off of 8, the clinician-rated PDSS is moderately effective in identifying patients with panic disorder (sensitivity: 83%; specificity: 64%; Shear et al, 2001).…”
Section: Pdss-srmentioning
confidence: 94%
“…Measures were selected for their psychometric properties and because they possess good sensitivity and specificity (Beck, Epstein, Brown, & Steer, 1988;Blanchard, Jones-alexander, Buckley, & Forneris, 1996;Connor et al, 2000;Cooper & Murray, 1998;Cox, Holden, & Sagovsky, 1987;Eberhard-gran, Eskild, Tambs, Opjordsmoen, & Samuelsen, 2001;Foa et al, 2002;Kleinknecht & Thorndike, 1990;Klorman, Weerts, Hastings, Melamed, & Lang, 1974;Meyer, Miller, Metzger R.L., Borkovec, 1990;Molina & Borkovec, 1994;The PTSD Checklist, 1993). All screening tool, with the exception of the Specific Phobia Questionnaire (see below), have been validated in settings similar to our own (Chambless, et al, 2011;Connor et al, 2000;Eberhard-gran et al, 2001;Evans, Spiby, & Morrell, 2015;Foa et al, 2002;McDonald & Calhoun, 2010;Newman, Holmes, Zuellig, Kachin, & Behar, 2006;Simpson, Glazer M, Michalski, Steiner, & Frey, 2014;Walker, Newman, Dobie, Ciechanowski, & Katon, 2002). For most of the anxiety disorders, screening instruments which have been validated for use in perinatal populations do not exist.…”
Section: Self-report Measuresmentioning
confidence: 99%
“…Only if these initial questions are answered in the affirmative, are the remaining questions administered. A score of 8.75 has been found to optimize sensitivity (89%) and specificity (100%) and was therefore selected for this research (Newman et al, 2006). The PDSR has been found to have excellent test-retest reliability, and convergent and discriminant validity (Newman et al, 2006).…”
Section: Panic Disorder Self-report (Newman Et Al 2006)mentioning
confidence: 99%